Integrated approach for geometric modeling and interactive visual analysis of grain structures. (April 2018) - Rodrigues, André Montes; Bardella, Fernando; Zuffo, Marcelo Knorich; Leal Neto, Ricardo Mendes
Abstract: This paper presents a novel approach that integrates geometric modeling and visual analysis of grain structures in an open source CAD system, aimed at educational purposes. An intuitive and simple automated modeling method produces valid polygonal representations of grain structures, by adopting a novel physics-based particle packing procedure with Voronoi-based tessellation. Models are structured to facilitate the development of interactive visualization prototypes in 3D interactive engines. Microstructural fidelity was pursued for the synthetic models to be accepted as representations of real materials. Meaningful sample's parameters such as mean number of neighbors and mean number of edges per face were replicated with acceptable precision, when compared to values obtained from 3D reconstruction of an alpha-iron sample. Domain-specific interactive experimental tools informed by learning and cognitive research sought to enhance spatial cognition of grain structures and support learning their fundamental features. Graphical abstract: Highlights: 2D visualization is limited to comprehend space-filling microstructures. Integration of modeling and visual analysis tools in an open source CAD application. Valid visualization-friendly grain structure models built in less than a minute. Specific tools presented superior learning value compared to earlier attempts. Interactive exploration allows better spatial cognition, enhancing grain structures learning.